KONSTRUKSI KEKERASAN DALAM POTRET PEMBERITAAN ISLAM DI KANAL INFORMASI INTERNET (Analisis Framing terhadap Website dan Portal Informasi Bergender Islam) - Ilham Prisgunanto (Communication, 2013)
Media are window that enable us to see beyond our immediate surroundings,intepreters that helps us make sense of experience that screen our parts of experience andfocus on others, mirrors that reflect ourselves block the truth. Any media always talk aboutgap political ideology behind messages from the text. Because of that this research talk aboutagenda of Moslem and any related issues in digital media (social media). the Umberella oftheories come from content analysis, agenda setting mass media. This research mix tworesearch models that quantitative model of conventional content analysis and qualitativemodel and for framing analysis Gamson and Modigliani model. The frame work of thisresearch at sociocultural tradition which focus for interaction between people. Collectingdata come from google search engine with keyword ISLAM and KEKERASAN and find5,620,000. After editing process just 100 reporting news from websites and information portalhad used for this research. Finding research exactly the same from the research before, thatmoslem get always bad image in people head. Beside it, Islamic scholar reinforce thatperceptions and more over create the new construction of bad perception's moslem becausethey follow the media agenda mainstream internasional mass media. And the bad perceptionof moslem would be impact to role's of political especially for leadearships profile of moslem